2013
DOI: 10.1093/schbul/sbt198
|View full text |Cite
|
Sign up to set email alerts
|

Differential Neurodevelopmental Trajectories in Patients With Early-Onset Bipolar and Schizophrenia Disorders

Abstract: Schizophrenia and bipolar disorders share not only clinical features but also some risk factors such as genetic markers and childhood adversity, while other risk factors such as urbanicity and obstetric complications seem to be specific to schizophrenia. An intriguing question is whether the wellestablished abnormal neurodevelopment present in many children and adolescents who eventually develop schizophrenia is also present in bipolar patients. The literature on adult bipolar patients is controversial. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
66
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 97 publications
7
66
1
1
Order By: Relevance
“…[1][2][3][4]38 We and others postulate that if onset of psychosis coincides with active maturational changes in a brain structure, then development of that particular brain structure will be most affected by the disease. 4,22 The current study indicates that if SSD starts after early adolescence, no differences are found in the parietal cortex of cases and controls. The parietal cortex reaches peak maturity in late childhood (around 7.5 y in girls and 9 in boys 4 ), and parietal abnormalities are present in very early-onset psychosis such as childhood-onset schizophrenia.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…[1][2][3][4]38 We and others postulate that if onset of psychosis coincides with active maturational changes in a brain structure, then development of that particular brain structure will be most affected by the disease. 4,22 The current study indicates that if SSD starts after early adolescence, no differences are found in the parietal cortex of cases and controls. The parietal cortex reaches peak maturity in late childhood (around 7.5 y in girls and 9 in boys 4 ), and parietal abnormalities are present in very early-onset psychosis such as childhood-onset schizophrenia.…”
Section: Discussionmentioning
confidence: 51%
“…Some studies have not found any differences between first-episode SSD and AFP patients, and many others do not include diagnostic subgroup comparisons. 22 Hence this finding warrants further replication. A previous study in first-episode AFP and schizophrenia patients aged 18-40 years also showed brain deficits confined to the subgenual cingulate in this specific subgroup.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The P3 is commonly believed to be an endogenous neuronal component that is dependent on the level of attention and arousal as well as the context in which a stimulus occurs (Polich, 2007). We acknowledge that this interpretation may be wrong, however, the existence of dissociable effects at latencies usually associated with higher order mechanisms may further support the notion that in adolescence, an active period of brain re-organization, different developmental pathways are materializing in schizophrenia and bipolar disorder with psychosis (Arango et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
“…It is thought that at a neuronal population level this reflects a maturation of the excitatory inhibitory balance in the temporal regions. Mapping changes in adolescence may, therefore, represent a uniquely sensitive way to understand the MMN response in schizophrenia and bipolar disorder against the developmental course of adolescence (e.g., Arango et al, 2014) Following our previous work (Dima et al, 2012) we used Magnetoencephalography (MEG) to quantify the MMN neuronal response in adolescents with schizophrenia (ASZ), in adolescents with bipolar disorder with psychosis (ABP) and in normally developing adolescents. MEG is able to image the brain at high temporal resolution, where the spatial resolution is typically better than EEG, thereby offering the potential to better delineate neural correlates of these disorders.…”
Section: Introductionmentioning
confidence: 99%